Clinical pharmacy service as a care strategy in intensive care: observational study - Caroline Falzoni SIMÕES; Gabriela Gonzalez MOSEGUI; Carla Valéria GUILARDUCCI (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objective: The present study aims to describe Pharmacotherapeutic Problems (PF) and Pharmaceutical Interventions (PI), as well as analyze the relationships between the number of pharmaceutical interventions and variables related to the patient, in order to explore the contribution of the pharmaceutical service to therapy care in intensive settings. Method: This is an analytical-descriptive, retrospective study, referring to data obtained through the pharmaceutical interventions form, filled out by residents during multidisciplinary rounds in the Adult Intensive Care Unit (ICU) of a large hospital in the city of Rio de Janeiro. These data were collected between August and December 2021. In addition to the analysis of the sample characteristics, pharmacotherapeutic problems, pharmaceutical interventions, team acceptability, direction of interventions and analysis of the correlation between the number of pharmaceutical interventions and variables such as sex, age, reasons for admission to the ICU and clinical outcome. Results: 116 forms were included and analyzed. The approximate average age of participants was 62 years, with 56% of patients being female and 85.3% having some comorbidity. 345 pharmaceutical interventions related to previously identified pharmacotherapeutic problems were carried out, directed to the multidisciplinary team, of which 93.1% were accepted. The most frequent intervention was "adequacy of the prescribed infusion rate" (135/39.4%). Statistical significance was found between the number of pharmacotherapy interventions for patients admitted to the ICU postoperatively and the clinical outcome. Conclusion: The large number of pharmacotherapeutic problems identified, the interventions carried out, the number of participating teams and the correlation between the variables analyzed suggest that the role of the pharmacist in multidisciplinary teams in intensive care brought benefits to the patients participating in the study. The high acceptance rate highlights the relevance of the Clinical pharmacist in promoting rational and safe pharmacotherapy and assistance in the care of critically ill patients.